Asymmetries between the Global North and South in leisure practices: vaccine tourism reconsidered. (20th December 2022) - Korstanje, Maximiliano E.
Over years, scholars have focused on travel behaviour and leisure practices worldwide. The advance of applied research, anyway, overlooks the fact that there are considerable asymmetries in leisure practices between the Global North and the peripheral South. These inequalities were mainly crystallised in the COVID-19 pandemic, a founding event that accelerated a global crisis in the health system. Thousand of peripheral tourists, coming from countries with low access to vaccination, flied to the North in quest of vaccines. The present paper explores not only the dilemmas of Argentinian tourists who travelled abroad to be inoculated, but also the contradictions and conflicts with Argentinian governments who imposed several restrictions to their return. As a result of this, many compatriots have been stranded abroad without food, assistance and lodging.